Efektivitas New Southern Policy dalam Memperkuat Kerjasama Keamanan Bilateral Korea Selatan-Indonesia pada Era Pemerintahan Presiden Moon Jae-In (2017-2022) - Shafiqa Aqeela Ramadhani (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2026)
This study aims to evaluate the success of the New Southern Policy (NSP) in enhancing security cooperation between South Korea and Indonesia during the administration of President Moon Jae-in (2017-2022). The NSP is South Korea's foreign policy designed to deepen relations with ASEAN countries and India through three main focuses: People, Peace, and Prosperity. This study uses a qualitative approach with a desk study method, relying on data such as journal articles, official government documents, and related academic publications. The analysis was conducted by applying the concepts of policy effectiveness and bilateral security cooperation to assess the extent to which the NSP succeeded in meeting its stated targets. The research findings indicate that the NSP made a significant contribution to strengthening security relations between South Korea and Indonesia through increased strategic security dialogue, collaboration in the defense sector, development of the defense industry, and technology transfer to support national defense. Furthermore, the NSP has enhanced Indonesia's position as South Korea's primary strategic partner in Southeast Asia. Therefore, the NSP can be considered successful in strengthening bilateral security cooperation between South Korea and Indonesia during the research period.